The Aquino alternative - Rajaretnam, M. (Singapore : ISEAS, 1986)
Papers presented at the Seminar on trends in the Philippines III organied by the Institute of Southeast Asian Studies, Singapore, 7 June 1986
Keywords: Philippines Congresses; Philippines Politics and government Congresses